Evaluación de las variables del desempeño cooperativo ahorro y crédito con enfoque en el buen vivir de la zona de Manabí - Cevallos Marín, Katherine Emilia (2017)
The main purpose of the study was to evaluate the cooperative saving and credit union variables performance with a focus on good living in central Manabí. Several activities were carried out, one of these was a visit to each of the saving and credit union in this area of Manabí, besides; a methodology which helped to select the performance variables to be evaluated was determined. The results led to propose an improvement plan, with the aim to increase efficiency among the unions. For all this, there were taken into consideration Cooperativism, Good living, Popular and Solidarity Economy, and Corporate Social Responsibility principles, these principles were added to a matrix that allowed to evaluate the unions administering surveys to managers, employees and partners. Then, weaknesses were identified as a baseline for the structuration of the improvement plan which consists of seven actions with a deadline, challenges, impact, prioritization and a person responsible. After analyzing the variables based on the selected principles as indicators, it concluded that 57% of savings and credit unions make use of these principles, while the others have undeveloped good living variables.